STRENGTHS AND WEAKNESSES OF THE REPRODUCTIVE BIOECONOMY MARKET: INSIGHTS FROM THE LITERATURE REVIEW - Đorđević , Biljana; Janičić, Radmila; Matejić, Bojana (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: The economy is a field that includes products, services, and trade, and reproductive bioeconomy refers to the field of reproduction and the ways of production, services, customers, and trade of reproductive cells and tissues. This research aimed to identify the key factors that shape the reproductive bioeconomy market and pinpoint opportunities for improvement as well as potential challenges. Accordingly, the study objective includes implementing an analysis to determine the Strengths, Weaknesses, Opportunities, and Threats in the reproductive bioeconomy market (SWOT analysis); this will enable the formulation of strategic guidelines for further development.Methods: A review of the literature published from 2017 to 2024 was carried out. A search of academic and scientific papers was conducted using the PubMed, Springer, and Elsevier databases, as well as the Google Scholar tool, to identify additional relevant sources. The following search string was used:”(“donating reproductive cells“ OR „gamete donation“ OR „oocyte donation “ OR „sperm donation“) AND („biomedical engineering“ OR „in vitro gamete production biotechnology“ OR „gamete cryobiology“ OR „gamete banks“ OR „cross-border reproductive care“ OR „Transnational gamete donation“) AND („parenthood delay“ OR „career impact on reproduction“ OR „one donor donates to several banks“ OR „non-traditional family“ OR „altruism“ OR „reproductive work“ OR „bioethics in donating reproductive cells“)“. The factors that have the greatest impact on the development of the reproductive bioeconomy market have been identified using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guide, and classified with the help of the SWOT instrument for strategic analysis into strengths, weaknesses, opportunities, and threats.Results: The review of the literature showed that the most influential forces of the reproductive bioeconomy are: (i) the strengths of the reproductive bioeconomy: the existence and development of biomedical engineering, the development of new technologies in biotechnology – Cryobiology, distribution and bioavailability of products – cryobanks; (ii) market opportunities: cross-border reproductive care (eng., Cross Border Reproductive Care), Transnational Gamete Donation Program (eng., Transnational Gamete Donation), and the diversity of consumers participating in the reproductive bioeconomy market; but also (iii) weaknesses: postponing parenthood to older ages, regulating the number of families per donor where different standards make monitoring difficult, the future formation of a complex, non-traditional, modern family; as well as (iv) potential threats in the form of unknown quality and future results, bioethical dilemmas, and that the commercialisation of reproductive work poses a threat to altruism.Conclusion: This research demonstrates significant potential for the reproductive bioeconomy in treating infertility and promoting family diversification. Before implementing the reproductive material donation program and establishing a national registry for domestic and foreign citizens who are potential beneficiaries of the donation program, the regulatory framework must be transparent and aligned with ethical and normative regulations.
Keywords: bioeconomy; biotechnology; SWOT analysis; reproductive market; gamete donation; PRISMA